Serum protein concentration in newborn calves fed with colostrum from cows with mastitis - Santos, Guilherme Gonçalves Fabretti [UNESP]; Deschk, Maurício [UNESP]; Silva, André Kielius Guedes [UNESP]; Pólo, Tatiane Silva [UNESP]; Marinho, Márcia [UNESP]; Peiró, Juliana Regina [UNESP]; Mendes, Luiz Cláudio Nogueira [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
The aim of this study was to evaluate the serum protein concentration in newborns fed with colostrum derived from healthy cows (n = 10), cows with subclinical mastitis (n = 10) and cows with clinical mastitis (n = 10). 30 Holstein cows were assigned to their respective groups according to macroscopic examination of colostral secretion, somatic cell count, CMT and presence of bacteria in colostrum samples. Blood samples of the calves were collected immediately after birth, at 24 and 48 hours after ingestion of colostrum. The total protein was measured by the biuret method and the concentrations of immunoglobulin A (IgA), immunoglobulin G (IgG), transferrin, albumin and haptoglobin was determined by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). No differences were observed amongst groups in the concentrations of albumin, total protein and IgA. In animals from cows with subclinical and clinical mastitis haptoglobin concentrations were higher than those of healthy animals. The concentrations of IgG and transferrin were significantly lower in calves from cows with mastitis. We concluded that the ingestion of colostrum from infected and uninfected glands from cows with mastitis (GII e GIII) is unlikely to be an important contributor to the high rate of failure of passive transfer of immunoglobulins in calves.
Proteinograma sérico de bezerros recém-nascidos alimentados com colostro de vacas com mastite
Keywords: Colostrum; Immunoglobulins; Mastitis; Passive transfer immunity